Blockchain Technology in Accounting Practice: Literature Review - Sunjaya, Robi; Putra, Jusintri; Ramadhan, Yanuar (International Journal of Economics Development Research (IJEDR), 2025)
This study seeks to elucidate the implementation of blockchain in accounting practices. It aims to explore the potential adoption of blockchain technology to enhance financial reporting. The research sample comprises relevant literature on blockchain adoption within the context of accounting and financial reporting. The methodology employed is a literature review, involving the reanalysis of prior research findings, theories, and concepts. The findings reveal that blockchain can improve efficiency, transparency, and robust security in transaction recording systems. Nevertheless, challenges persist in its application, including limitations in accountants’ proficiency to utilize blockchain technology.